2021
DOI: 10.3390/genes12050658
|View full text |Cite
|
Sign up to set email alerts
|

LINCking the Nuclear Envelope to Sperm Architecture

Abstract: Nuclear architecture undergoes an extensive remodeling during spermatogenesis, especially at levels of spermatocytes (SPC) and spermatids (SPT). Interestingly, typical events of spermiogenesis, such as nuclear elongation, acrosome biogenesis, and flagellum formation, need a functional cooperation between proteins of the nuclear envelope and acroplaxome/manchette structures. In addition, nuclear envelope plays a key role in chromosome distribution. In this scenario, special attention has been focused on the LIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 149 publications
(191 reference statements)
0
20
0
Order By: Relevance
“…Thus, it is more likely that DNALI1 associates with the manchette microtubules through dynein heavy chain 1. Another function of the manchette is to help shape the head of developing spermatids (47, 48). Like the Meig1 and Pacrg mutant mice, the Dnali1 cKO mice also developed abnormal sperm heads, which further supports the claim that DNALI1 is involved in the construction of a functional manchette.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is more likely that DNALI1 associates with the manchette microtubules through dynein heavy chain 1. Another function of the manchette is to help shape the head of developing spermatids (47, 48). Like the Meig1 and Pacrg mutant mice, the Dnali1 cKO mice also developed abnormal sperm heads, which further supports the claim that DNALI1 is involved in the construction of a functional manchette.…”
Section: Discussionmentioning
confidence: 99%
“…Important biological processes including cytoarchitecture organization, chromatin remodeling, and the optimal maintenance of male fertility are under the control of ANKRD proteins ( Cunhaa and Mohler, 2009 ; Argudo et al, 2019 ; Tang et al, 2020 ; Manfrevola et al, 2021a ). In this scenario, particular attention has been given to ANKRD31, a key regulator of male meiosis and epididymal sperm maturation ( Boekhout et al, 2019 ; Acquaviva et al, 2020 ; Manfrevola et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, mechanotransduction pathways, through the formation of cytoskeletal–nucleoskeletal connections, transduce extracellular mechanical forces into biochemical signals propagating them along the cytoskeleton to the nuclear envelope, in order to regulate chromatin organization and gene expression, as the final biological effect ( Uhler and Shivashankar, 2017 ; Manfrevola et al, 2021a ). New insights regarding the involvement of ANKRDs in mechanotransduction have been reported as ANKRDs, interacting with mechanosensitive channels, are required for the cytoplasmic transmission of mechanosensory activity in neurons ( Argudo et al, 2019 ; Tang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bridging the nuclear envelope to link the nucleoskeleton to the cytoskeleton is achieved by the binding to KASH-domain proteins that interact with their N-terminal ends with the cytoskeleton. Although currently no specific KASH-domain proteins have been identified that are involved in HTCA formation, SUN5 interacts with the KASH-domain protein nesprin3 in spermatozoa, indicating that the HTCA comprises at least the SUN5/nesprin3 LINC complex [ 167 , 201 , 202 ].…”
Section: The Protein Components Of the Connecting Piece And Their Relevance For The Head-to-tail Linkage And Male Fertilitymentioning
confidence: 99%